Restricciones en la financiación de la innovación: El caso de la comunidad Valenciana - Luis Martinez Chafer; Francesc Xavier Molina Morales (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2011)
Financing has been considered as a critical requirement for firm innovation projects. However, these projects are typically characterized by a high degree of uncertainty, complexity and specificity. As a consequence companies may find difficulties to obtain support from financial markets. By a Social Network Analysis we aim to map and interpret the role of the different credit institutions in the Valencia region considering its network attributes. Findings suggest weakness of traditional banking and venture capital firms.
Keywords: O31; 330; social network analysis; innovation; credit rationing; Valencia region; R&D